TRAINING AND TEACHING AL-QURAN READING AND WRITING AT MADRASAH DINIYAH NURUSSYABAB : TRAINING AND TEACHING AL-QURAN READING AND WRITING AT MADRASAH DINIYAH NURUSSYABAB - Siskha Putri Sayekti; M. Farhan Humaidi; Hasna Ardianti (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2022)
The service carried out at Madrasah Diniyah Nurussyabab Rangkapan Jaya Baru, aims to the first, improve the ability to read Al-Quran at Madrasah Diniyah Nurussyabab, seconda forms afrom of concern for the community service team and lectures in implementing the Tridharma of higher education, namely community service. The approach taken during this PKM activity is thematic, systematic, flexibility learning and religious guidance. From the results of the dedication and discussion,it was concluded that (1) The number of illiteracy rates of the Al-Quran in children at Madrasah Diniyah Nurussyabab were still high, and (2) The cause of the high number of Al-Quran illiteracy rates is ore on motivation and lack of internal interest in learning the Al-Quran. (3) The Iqra method is a method that is considered effective to be used in order to eradicate illiteracy in the Qur’an children. In this PKM, santri are all to memorize short suras, practice prayers, call to prayer and provide insight to the students in order to understand Islamic education well.